Intestinal obstruction caused by a clamped persistent omphalomesenteric duct in congenital hernia into the umbilical cord - Zlatan Zvizdic (9212371) (2023)
Other Information Published in: Pediatrics International License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/ped.14598